External and internal forcings controlled the precipitation patterns in eastern China over the past millennium - Li, Hai; Tang, Jianhui; Zhong, Yi; Ning, Liang; Liu, Jiabo; Sun, Chijun; Zhang, Weijie; Chou, Yu-Min; Liu, Qingsong (Frontiers in Marine Science, 2025)
The Asian Summer Monsoon provides critical water source to over a billion people. However, there is mounting evidence regarding how precipitation associated with the Asian Summer Monsoon varies spatially and temporally, prompting further exploration of the underlying mechanisms. Here, we reconstruct a 2900-year summer precipitation record through grain-size and clay analyses of core M5-8 retrieved from the Bohai Sea in China. Our records indicate that the warm (cold) phase of the Atlantic Multidecadal Variability significantly increases (decreases) summer precipitation in North China through atmosphere-ocean feedback and circum-global teleconnection. Over the past millennium, eastern China exhibited a distinctive tripole pattern of summer precipitation. During the Medieval Climate Anomaly, it exhibited a positive-negative-positive structure in North, Central, and South China, respectively. In contrast, during the Little Ice Age, the pattern flipped to a negative-positive-negative structure. These patterns were influenced by external forcings, including solar activity and volcanic eruptions, which directly influenced atmospheric circulation patterns and modulated internal climate variability. Our study provides an improved understanding of the summer precipitation variability in East Asia, and emphasizes the external and internal forcings in shaping the spatial patterns of monsoon precipitation.